Intraregional Migration in South America: Trends and a Research Agenda - Cerrutti, Marcela Sandra (2015)
This article contributes to the global dialogue attempting to incorporate South-South intraregional migration into policy and academic discussions by reviewing the dynamics, characteristics, and legalcontexts of interregional migration in South America. We first present the historical formation of migratory subsystems and identify emerging trends. We then organize our revision along the main theoretical issues surrounding international migration and their significance in the region. These issues include motivation, contexts of origin and reception, migration dynamics, gender, race and ethnicity, immigrant adaptation, and migration policies. Next, we consider the study of South American migrations, both internal and international, to be a research agenda with significant potential to deepen our understanding of migrations in general and to propose new theoretical orientations that go beyond the questions already identified in the mobility from poorer to wealthier countries. We conclude with suggestions for a research agenda devoted to interregional migration in South America.